ANALISIS KINERJA KEUANGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED PADA PT MEDCO ENERGI INTERNASIONAL TBK - Tambunan, Joe'l Philips; Jalaludin Sayuti; Yusleli Herawati (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study analyzes the financial performance of PT Medco Energi Internasional Tbk for the period 2019–2023 using the Economic Value Added (EVA) and Market Value Added (MVA) approaches. The analysis is based on the company’s financial statements through calculations of NOPAT, Invested Capital, WACC, and Company Value. The results show that EVA was only positive in 2022, amounting to Rp 2,717.95 billion, while in 2019, 2020, 2021, and 2023, it was negative, with the lowest value recorded in 2020 at Rp -6,952.09 billion due to low capital efficiency and operational pressure. MVA also showed negative values for five consecutive years, indicating the company's failure to create market value exceeding its invested capital. The lowest MVA occurred in 2023 at Rp -60,575 billion, caused by a significant increase in capital that was not matched by a rise in market value. These findings indicate that the company’s financial performance has not been optimal, and improvements in capital efficiency, operational performance, and business strategies are necessary to enhance firm value and gain investor confidence.